2016
DOI: 10.1097/sla.0000000000001559
|View full text |Cite
|
Sign up to set email alerts
|

Results of More Than 11,800 Sleeve Gastrectomies

Abstract: Owing to the growing experience a constant decrease in the leakage rate after SG has been observed. Staple line disruption may still lead to sepsis, multiorgan dysfunction, and increased mortality. The results of the current study demonstrated that there are factors that increase the risk of leakage and which would enable surgeons to define risk groups, select patients more carefully, and offer closer follow-up during the postoperative course with early recognition and adequate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(27 citation statements)
references
References 18 publications
1
24
0
1
Order By: Relevance
“…The lack of adherence to follow-up was reported previously, and it can be related to several issues, including the distance to the medical office and a lack of trust or rapport with the surgeon or the medical team[46]. However, the most relevant strength of this study is that all patients underwent a standardized LSG operative technique, first, because surgeon expertise is a key issue to lower the complications rate[13,24] and second, because there were no technical differences that may influence the weight loss results. We always tried to perform a more restrictive LSG by using a thinner bougie and beginning the dissection 3 cm from the pylorus to achieve greater weight loss, as suggested by Baltasar et al[8,31].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The lack of adherence to follow-up was reported previously, and it can be related to several issues, including the distance to the medical office and a lack of trust or rapport with the surgeon or the medical team[46]. However, the most relevant strength of this study is that all patients underwent a standardized LSG operative technique, first, because surgeon expertise is a key issue to lower the complications rate[13,24] and second, because there were no technical differences that may influence the weight loss results. We always tried to perform a more restrictive LSG by using a thinner bougie and beginning the dissection 3 cm from the pylorus to achieve greater weight loss, as suggested by Baltasar et al[8,31].…”
Section: Discussionmentioning
confidence: 92%
“…The method for doing so is still a matter of debate[21]. Some reports showed no differences between oversewing of the staple line and the use of buttresses[22-24]. However, a systematic review of 88 included studies representing 8920 patients[15] found that the leak rate in LSG was significantly lower using absorbable membrane (Seamguard ® ) staple-line reinforcement (1.1%) than was oversewing (2.0%), bovine pericardial strip (BPS-Peristrips ® ) reinforcement (3.3%), or no reinforcement (2.6%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is further corroborated by Parikh et al [14] who concluded that performance of the leak test did not seem to impact the leak rate (P = 0.454). Some studies have even suggested that intra operative leakage testing was a risk factor for leakage with an odds ratio of 2.26 [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic sleeve gastrectomy is at risk of resection line leaks in 1.1% to 6.5% of cases according to world literature [24]. In terms of pathogenesis, the leak is caused by a combination of: a) local factors – partial stomach wall ischemia, amount of stomach tissue caught in the staple, size of the staples, and staple failure, and b) general factors – metabolic disorders, abdominal obesity, etc.…”
Section: Discussionmentioning
confidence: 99%